American Indian women cancer survivors' experiences of community support in a context of historical oppression. Issue 3 (2nd July 2020) - Roh, Soonhee; McKinley, Catherine E.; Liddell, Jessica L; Lee, Yeon-Shim; Yun Lee, Hee
ABSTRACT: This qualitative descriptive study examined the gap in knowledge on American Indian (AI) women cancer survivors' perceptions of and experiences of AI community support. The sample included 43 AI women cancer survivors in the Northern Plains region. In total, 21% ( n = 9) of participants perceived support from their AI community; 69% ( n = 29) expressed some unmet needs; close to half of participants (43%, n = 18) indicated an absence of support. Historical oppression may have undermined the ability of communities to provide support to cancer survivors. Further investment in community infrastructure is warranted to reverse centuries of historical oppression.